2019
DOI: 10.18632/aging.102366
|View full text |Cite
|
Sign up to set email alerts
|

TIMP1 mRNA in tumor-educated platelets is diagnostic biomarker for colorectal cancer

Abstract: Platelets have been shown to promote the growth of tumors, including colorectal cancer. The RNA profile of tumor-educated platelets has the possibility for cancer diagnosis. We used RNA sequencing to identified the gene expression signature in platelets from colorectal cancer patients and healthy volunteers. We then verified the selected biomarkers from the RNA sequencing in a two-step case-control study using quantitative reverse-transcription polymerase chain reaction. We found that TIMP1 mRNA levels are hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
42
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(46 citation statements)
references
References 18 publications
4
42
0
Order By: Relevance
“…After chemotherapy, high expression levels of TIMP1 in the serum have been closely related to the decline over survival (OS) [ 38 ]. Moreover, knockdown of TIMP1 leads to decreased proliferation of HT29 cells [ 39 ]. Huang et al [ 40 ], Zeng et al [ 41 ], and Zuo et al [ 42 ] demonstrated that the expression levels of TIMP1 may be negatively correlated with the prognosis of COAD patients.…”
Section: Discussionmentioning
confidence: 99%
“…After chemotherapy, high expression levels of TIMP1 in the serum have been closely related to the decline over survival (OS) [ 38 ]. Moreover, knockdown of TIMP1 leads to decreased proliferation of HT29 cells [ 39 ]. Huang et al [ 40 ], Zeng et al [ 41 ], and Zuo et al [ 42 ] demonstrated that the expression levels of TIMP1 may be negatively correlated with the prognosis of COAD patients.…”
Section: Discussionmentioning
confidence: 99%
“…After chemotherapy, high expression levels of TIMP1 in the serum have been closely related to the decline over survival (OS) [38]. Moreover, knockdown of TIMP1 leads to decreased proliferation of HT29 cells [39]. Huang [40], Zeng [41], and Zuo [42] et al demonstrated that the expression levels of TIMP1 may be negatively correlated with the prognosis of COAD patients.…”
Section: Discussionmentioning
confidence: 99%
“…al [13] have identified RNA profiles of TEPs can be used to diagnose cancer patients with 96% accuracy through NGS based on 283 blood platelet samples, isolated from healthy controls and patients with cancer. Furthermore, recent studies have demonstrated that TIMP1 and TGA2B mRNA in tumor-educated platelets are diagnostic biomarkers for colorectal cancer and lung cancer respectively [19,20]. In this study, integrating the NGS datasets, GSE68086 and GSE89843, downloaded from GEO datasets, we identified 43 TEPs genes were consistently differential expressed through bioinformatic analysis, and they were involved in many biological processes including protein binding, extracellular matrix, cellular protein metabolic process, mitochondrial outer membrane and innate immune response in mucosa, and [40,41].…”
Section: Discussionmentioning
confidence: 99%
“…are diagnostic biomarkers for colorectal cancer and lung cancer respectively [19][20][21][22]. However, these reports have some limitations, including limited clinical samples, lacked cancer stage prediction and through them, only one single cancer species could be predicted.…”
Section: / 36mentioning
confidence: 99%